Cooperative Control of Bimanual Continuum Robots for Automated Knot-Tying in Robot-Assisted Surgical Suturing - Quaicoe, Enoch; Nada, Ayman; Ishii, Hiroyuki; El-Hussieny, Haitham (Journal of Robotics and Control (JRC), 2024)
Knot-tying, a crucial yet intricate surgical task, remains a challenge in Robot-assisted Minimally Invasive Surgery (RAMIS) performed under teleoperation. While existing studies on automated knot-tying mostly focus on rigid-link robots, whose dexterity, adaptability, and inherent safety in RAMIS are outperformed by continuum robots, this research takes a novel approach by developing a unique cooperative control scheme for bimanual continuum robots, specifically designed for automated knot-tying tasks in RAMIS. We meticulously plan two effective knot-tying trajectory scenarios and develop the cooperative control scheme for the bimanual continuum robots, leveraging the well-known Jacobian transpose kinematic algorithms to ensure their precise and collaborative knot-tying trajectory tracking performance. The control scheme incorporates a switching mechanism to guarantee the robots’ collaboration and synchronous operation during the knot-tying trajectory tracking process. The effectiveness of our cooperative control scheme is illustrated through simulation studies using MATLAB/Simulink in terms of trajectory tracking performance. Meanwhile, ten Monte Carlo simulations are conducted to analyze the system’s robustness against pulse disturbances that could occur in surgical settings. All ten simulations returned similar error values despite the increasing disturbance levels applied. The results not only demonstrate the seamless collaboration and synchronous operation of the bimanual continuum robots in precisely tracking the pre-planned knot-tying trajectories with errors less than 0.0017 m but also highlight the stability, effective tuning and robustness of our cooperative control system against pulse disturbances. This study demonstrates precision, robustness, and autonomy in bimanual continuum robotic knottying in RAMIS, promising safe robot-patient interaction and reduced surgeon workload and surgery time.